Adaptation of the inflammatory immune response across pregnancy and postpartum in Black and White women. (April 2016) - Gillespie, Shannon L.; Porter, Kyle; Christian, Lisa M.
Highlights: We examined LPS-stimulated cytokine responses across pregnancy and postpartum. IL-6, TNF-α, and IL-1β production increased from early to late pregnancy. Subsequent declines approaching early pregnancy values were seen at postpartum. Minimal differences were observed among Black versus White women. Future data on adaptation in healthy versus disordered pregnancy would be informative. Abstract: Pregnancy is a period of considerable physiological adaption in neuroendocrine, cardiovascular, as well as immune function. Understanding of typical changes in inflammatory immune responses during healthy pregnancy is incomplete. In addition, despite considerable racial difference in adverse pregnancy outcomes, data are lacking on potential racial differences in such adaptation. This repeated measures prospective cohort study included 37 Black and 39 White women who provided blood samples during early, mid-, and late pregnancy and 8–10 weeks postpartum. Peripheral blood mononuclear cells were incubated with lipopolysaccharide (LPS) for 24 h and supernatants assayed by electrochemiluminescence to quantify interleukin(IL)-6, tumor necrosis factor(TNF)-α, IL-1β, and IL-8 production. While no changes were observed in IL-8 production over time, significant increases in IL-6, TNF-α, and IL-1β production were observed from early to late pregnancy, with subsequent declines approaching early pregnancy values at postpartum ( ps  < 0.05). Overall, inflammatory response patterns were highly similar among Black versus White women. However, Black women had greater TNF-α production during mid-pregnancy ( p  = 0.002) and marginally lower IL-1β production at postpartum ( p  = 0.054). These data show a clear trajectory of change in the inflammatory immune response across pregnancy and postpartum. In this cohort of generally healthy women, Black and White women exhibited minimal differences in LPS-stimulated cytokine production across the perinatal period. Future prospective studies in Black and White women with healthy versus adverse outcomes (e.g., preeclampsia, preterm birth) would inform our understanding of the potential role of immune dysregulation in pregnant women and in relation to racial disparities in perinatal health.